2021
DOI: 10.18805/ijare.a-614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Density and Row Spacing on Yield and Yield Components of Peanut (Arachis hypogaea L.) on the Coastal Sandy Land Area in Nghe An Province, Vietnam

Abstract: Background: Understanding the effects of different plant densities and row spacing on yield and yield components of peanut L14 is essential for designing and adjusting management practices to improve yield. Methods: Five planting densities were tested in Randomized Complete Block Design with three replications in 2019 spring crop on the coastal sandy land area in Dien Chau district, Nghe An, Vietnam. Result: The different density treatments affect the growth, development and yield of the peanut variety L14. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Other similar fndings of Khan et al [39] for onion and Streck et al [43] for cassava and Neri et al [48] for pineapple also confrmed that the closest spacing or the highest planting density produced the highest yield, while the widest plant spacing or the lowest planting density had the lowest yield. In general, the present result is consistent with the report of Minh et al [42] that showed the tallest peanut height was measured in the closest spacing (25 cm × 15 cm) or the highest plant density (45 plants m −2 ), while the shortest was noted in the widest (25 cm × 35 cm) or the lowest plant density (25 plants m −2 ). In line with our fnding and the aforementioned results, Zibelo et al [44] for okra plants and Wu et al [41] for perilla sprouts reported similar fndings related to spacing or planting density.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Other similar fndings of Khan et al [39] for onion and Streck et al [43] for cassava and Neri et al [48] for pineapple also confrmed that the closest spacing or the highest planting density produced the highest yield, while the widest plant spacing or the lowest planting density had the lowest yield. In general, the present result is consistent with the report of Minh et al [42] that showed the tallest peanut height was measured in the closest spacing (25 cm × 15 cm) or the highest plant density (45 plants m −2 ), while the shortest was noted in the widest (25 cm × 35 cm) or the lowest plant density (25 plants m −2 ). In line with our fnding and the aforementioned results, Zibelo et al [44] for okra plants and Wu et al [41] for perilla sprouts reported similar fndings related to spacing or planting density.…”
Section: Discussionsupporting
confidence: 93%
“…Tis fnding also supported by Wu et al [41] who reported that high plant density (1,450 plants m −2 ) signifcantly increased content of total chlorophyll, net photosynthesis rate, and fnally perilla yield [41]. Likewise, the highest LAI was recorded during fowering, pod formation, and harvesting periods in the closest spacing (25 cm × 15 cm) or the highest plant density (45 plants m −2 ), while the lowest was noted in the widest (25 cm × 35 cm) or the lowest plant density (25 plants m −2 ) [42]. In the same way, various earlier studies further by Streck et al [43] for the cassava plant, Grigg et al [36] for E. marginata, and Zibelo et al [44] for the okra plant found that that the closest spacing had the highest LAI, while the widest plant spacing showed the lowest LAI.…”
Section: Discussionmentioning
confidence: 88%
“…A narrow-row planting (30 cm) gave a significantly higher yield (3739 kg/ha) than wide-row (60 cm) planting (1903 kg/ha) in Pakistan [22]. Plant densities and row spacing of 350,000 plants per hectare (25 cm × 25 cm with two plants per hill) and 400,000 plants per hectare (25 cm × 20 cm with two plants per hill) were found appropriate for high yield in Vietnam [10]. In Australia, Bell et al [23] reported an increase in total dry matter and pod yields with increasing plant density under fully irrigated conditions, though cultivars differed in their response, with the best cultivar, chico, recording the highest total dry matter and pod yields at 352,000 plants per hectare.…”
Section: Effect Of Plant Density On Yield and Its Componentsmentioning
confidence: 92%
“…Optimum plant density (spacing between plants) is among the critical crop management practices for obtaining a high groundnut yield and profitable economic returns. Various authors have indicated that maximum or optimum yields of groundnut were obtained with higher plant densities, e.g., [7][8][9][10][11]. In India, the optimum population of 330,000 plants per hectare (30 cm × 10 cm) for Spanish/Valencia cultivars and 148,000 plants per hectare (45 cm × 15 cm) for Virginia cultivars were reported [7].…”
Section: Introductionmentioning
confidence: 99%